THE SOUTHWESTERN LIMES OF ROMAN DACIA AND BEYOND - NEW SURVEYS AND EXCAVATIONS - Eduard Nemeth (Journal of Ancient History and Archaeology)
This paper presents the results of a research project on the southwestern frontier of Roman Dacia, which was an external frontier of the Roman Empire in this area. The research aimed to investigate and locate on the ground all Roman military sites with modern devices (GPS) and establish the elements of the ancient landscape that had an influence on the choice of particular locations for the Roman forts. Also, the Roman military sites have been placed on geo-referenced maps. Another goal was to locate and investigate the great earth ramparts from nowadays southwestern Romania (so-called "Roman walls") and try to see whether there is a relation between them and the forts on one side and the many sites (cemeteries and settlements) of the Sarmatian Iazyges. This people, that lived to the west from Roman Dacia, penetrated the marshy plains east of the river Tisza much earlier than the researchers previously supposed, that is right after the Marcomannic wars (after 180 AD) and not only at the end of the 3rd century AD.